2017
DOI: 10.1111/pde.13084
|View full text |Cite
|
Sign up to set email alerts
|

Atopic Dermatitis in Israeli Adolescents from 1998 to 2013: Trends in Time and Association with Migraine

Abstract: This large cross-sectional study demonstrates the increasing prevalence of AD in adolescents and its relation to other allergic diseases and migraine. It is hoped that greater awareness of the distinctive epidemiologic characteristics of this population will lead to better recognition and management of the disease and its comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…It is possible that individuals with severe AD have a higher prevalence of adverse cardiovascular events because of shared associated factors such as obesity, smoking, hypertension, and diabetes. Migraine has previously been linked to allergic diseases such as asthma and allergic rhinitis, and some studies have reported an association with AD in children and adolescents as well [7,8]. Our study adds new knowledge about the increased prevalence of migraine and headache in adults with AD.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…It is possible that individuals with severe AD have a higher prevalence of adverse cardiovascular events because of shared associated factors such as obesity, smoking, hypertension, and diabetes. Migraine has previously been linked to allergic diseases such as asthma and allergic rhinitis, and some studies have reported an association with AD in children and adolescents as well [7,8]. Our study adds new knowledge about the increased prevalence of migraine and headache in adults with AD.…”
Section: Discussionmentioning
confidence: 55%
“…Further, smoking has been reported to be associated with both AD and COPD, suggesting that it may be a shared risk factor for the two diseases. Co-occurrence of migraine has also been observed in individuals with AD [7,8].…”
Section: Introductionmentioning
confidence: 93%
“…Patients with moderate to severe AD were defined as patients who had received systemic corticosteroids. 13–16 The exclusion criterion was any diagnosis of a keloid (ICD-9-CM code 701.4) before the index date. 17 During the follow-up period, the occurrence of keloid was defined as ≥3 keloid diagnoses in outpatient visits or ≥1 keloid diagnoses in inpatient medical service.…”
Section: Methodsmentioning
confidence: 99%
“…15,16 In Canada, the prevalence of AD in children from Indigenous communities is higher than the prevalence reported in major cities, ranging from 16.5% to 27.6% in Iqaluit and a Native Reserve in Labrador. [17][18][19] In addition to racial differences, sociodemographic and economic determinants of health may play a role in AD prevalence, [20][21][22] with most studies reporting a correlation between higher socioeconomic status and increased AD prevalence. 23…”
Section: Epidemiologymentioning
confidence: 99%